The Ethics of Continued Life‐Sustaining Treatment for those Diagnosed as Brain‐dead. (16th July 2015) - du Toit, Jessica; Miller, Franklin
Abstract: Given the long‐standing controversy about whether the brain‐dead should be considered alive in an irreversible coma or dead despite displaying apparent signs of life, the ethical and policy issues posed when family members insist on continued treatment are not as simple as commentators have claimed. In this article, we consider the kind of policy that should be adopted to manage a family's insistence that their brain‐dead loved one continues to receive supportive care. We argue that while it would be ethically inappropriate to continue to devote scarce acute care resources to such patients in a hospital setting, it may not be ethically inappropriate for patients to receive these resources in certain other settings. Thus, if a family insists on continuing to care for their brain‐dead loved at their home, we should not, from a policy perspective, interfere with the family's wishes. We also argue that healthcare professionals should make some effort to facilitate the transfer of brain‐dead patients to these other settings when families insist on continued treatment despite being informed about the lack of any potential for recovery of consciousness. Our arguments are strengthened by the fact that patients in a persistent vegetative state, who, when correctly diagnosed, also have no potential for recovery of consciousness, are routinely transferred from hospitals to nursing homes or long‐term care facilities where they continue to be ventilated, tube fed and to receive other supportive care. We also briefly explore the question of who should be responsible for the costs of such treatment at the long‐term care facility.